DIGITAL EDUCATIONAL RESOURCES AND MOOCS IN MODERN HIGHER EDUCATION: STRUCTURE, FUNCTIONS, AND PEDAGOGICAL POTENTIAL (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article examines the role and significance of digital educational resources (DERs) and Massive Open Online Courses (MOOCs) in contemporary higher education systems. It analyzes the structure, composition, and functional characteristics of institutional digital learning resources, including lecture materials, methodological manuals, electronic textbooks, and large-scale full-text databases provided by international publishers. The study also explores the concept of electronic libraries as integrated information systems designed to ensure efficient access, organization, and long-term preservation of digital knowledge resources. Special attention is given to the pedagogical advantages of DERs, such as enhanced accessibility, multimedia integration, unlimited information capacity, and continuous availability. Furthermore, the article discusses MOOCs as a rapidly developing form of distance education that supports lifelong learning and broadens access to quality education worldwide. The analysis highlights their key features, including flexibility, interactivity, cost-effectiveness, and alignment with modern labor market demands. At the same time, certain limitations are identified, particularly related to learner self-regulation and the absence of strict instructional control. The findings demonstrate that both DERs and MOOCs significantly contribute to improving the quality, accessibility, and efficiency of modern educational processes.